Threshold Space: Ruang Antara dari Alun-alun Cicendo, Bandung - Amelia, Kiki Putri; Cardiah, Tita; Liritantri, Widyanesti; Mahendra, Bintang; Ammara, Kinanti (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 11 No 1 (2024): April 2024, 2024)
Threshold space in Cicendo Square is critical in facilitating accessibility and creating the impression of an excellent public open space. By considering entrances, transitions, and building access, threshold space design must consider various considerations, including openness in design, sequences, geometry, topography, distinctive material, and provision of appropriate furniture to improve the quality of open spaces public. Taking a case study of Alun-alun Cicendo (Steel Plaza) in Bandung City as its case study, this research has two objectives. The first is to analyze the role of threshold space as an intermediary space in creating accessibility and spatial impressions in public open spaces. The second is to identify and determine factors in designing an adequate threshold space to improve the quality of public open space. This research uses a qualitative approach with descriptive analysis and interpretation. Research findings show that the analyzed parameters, namely delimitation, sequence, geometry, topography, materiality, and seating facilities, play an essential role in creating an adequate transitional space in Cicendo Square. In line with the dynamic of the existing functions and activities, these factors also contribute to creating attractive and high-quality public open spaces and increasing interest and public participation in using Cicendo Square. Keywords: threshold space; public open space Abstrak Threshold space di Alun-alun Cicendo memainkan peran kunci dalam memfasilitasi aksesibilitas dan menciptakan kesan ruang terbuka publik yang baik. Dengan mempertimbangkan entrance , transisi, dan akses bangunan, desain threshold space harus memperhitungkan faktor-faktor seperti keterbukaan dalam desain sequences , geometri, topografi, kekhasan bahan, dan penyediaan furnitur yang sesuai untuk meningkatkan kualitas ruang terbuka publik. Dengan menjadikan Alun-alun Cicendo (Steel Plaza) di Kota Bandung sebagai studi kasus, penelitian ini memiliki dua tujuan. Pertama untuk menganalisis peran threshold space sebagai ruang perantara dalam menciptakan aksesibilitas dan kesan ruang pada ruang terbuka publik. Kedua, untuk mengidentifikasi faktor-faktor penentu dalam merancang threshold space yang efektif untuk meningkatkan kualitas ruang terbuka publik. Penelitian ini menerapkan pendekatan kualitatif dengan analisis deskriptif dan interpretasi. Temuan penelitian menunjukkan bahwa parameter-parameter yang dianalisis, yaitu delimitasi, sekuens, geometri, topografi, materialitas, dan sarana duduk, berperan penting dalam menciptakan ruang transisi yang efektif pada Alun-alun Cicendo. Beriringan dengan dinamika dari beragam fungsi dan aktivitas yang ada, faktor-faktor ini berkontribusi terhadap penciptaan ruang terbuka publik yang menarik dan berkualitas, dan peningkatan minat serta partisipasi masyarakat dalam menggunakan Alun-alun Cicendo. Kata kunci: threshold space ; ruang terbuka publik